Ancaman Zoonosis : Infeksi Plasmodium knowlesi pada Manusia - Saroh, Dewi; Haryatmi, Dwi (Jurnal Farmasi (Journal of Pharmacy), 2019)
Plasmodium knowlesi is one of the blood protozoa that can cause malaria. P. knowlesi initially only infected long-tailed macaques, but now it can cause zoonoses and infect humans. P. knowlesi can infect human body singly or mix infection with other parasites. This paper aims to provide a review of the morphology, prevalence, diagnosis, and treatment of P. knowlesi infections. The results of the review found that diagnosis of P. knowlesi can be established by PCR examination because diagnosis by microscopic can cause misidentification and lead to errors in diagnosis. Transmission of P. knowlesi to humans can occur through the bite of Anopheles Leucosphyrus Group mosquito. The prevalence of P. knowlesi to date has been found in the Southeast Asian region specifically in Malaysia. Treatment of malaria due to P. knowlesi without complications can be given with ACT therapy or with a combination of chloroquine and primaquine.